The impact of occupational health and safety and workstation design on total quality management and worker productivity. - Chiang, JH (Philippine Industrial Engineering Journal)
The integration of occupational health and safety, workstation design, total quality management elements (namely, customer focus, continuous improvement, and teamwork) and productivity has received increasing attention from scholars and practitioners. The questions of how OHS and workstation design relate to TQM and TQM relate to productivity are at the center of this discussion. Data were obtained through survey questionnaires administered to employees of a food factory and respondents are categorized into three subgroups by age and current experience for ANOVA analysis. In OHS and customer focus, the oldest and the youngest groups are significant differences in mean. The oldest is relatively more sensitive to positive effects of OHS and customer focus problems than the youngest. The most and the moderate current experienced respondents show significant differences in mean on OHS, and the moderate is relatively more sensitive to positive effects of OHS problems than the most. The relationships among variable are also discussed. It shows that workstation design was significantly related to OHS. OHS was significantly related to customer focus. Customer focus was significantly related productivity. Finally, directions for future research are proposed.